Use of cerebrospinal fluid CXCL13 concentration for diagnosis and monitoring of neurosyphilis: a three-case report - Carvalho, Ricardo de Souza; Rangel, Isabelle de Carvalho; Soane, Michel Moraes; Lopes, Márcia Quinhones Pires; Ferry, Fernado Raphael de Almeida (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Previous retrospective studies have demonstrated that the concentration of chemokine ligand CXCL13 in cerebrospinal fluid (CSF-CXCL13) is a promising biomarker in the diagnosis of neurosyphilis and, additionally, in the monitoring of therapeutic efficacy. Objective: To describe three cases of patients with neurosyphilis (NS) treated at Hospital Universitário Gaffrée e Guinle, in Rio de Janeiro, Brazil, with suspected active syphilis with neurological symptoms. Case report: Three patients from Rio de Janeiro, Brazil, were investigated for symptomatic NS. The concentration of CSF-CXCL13 was prospectively performed by enzyme-linked immunosorbent assay (ELISA) in all participants at baseline and in follow-up visits at 3 months after therapy. CSF-CXCL13 concentrations were significantly higher in all three patients with established NS. The CSF-CXCL13 concentrations decreased after 3 months of therapy compared to baseline in all cases reported. The added high concentration of CSF-CXCL13 plus CSF-TPHA reactivity above 1:40 titer agreed with the diagnosis of NS in 100% of the cases. Conclusion: In this case series, we present three cases of NS diagnosed using CXCL13 in CSF as a complementary test. These case series suggest that the clinical use of CSF-CXCL13 is useful as a supplementary biomarker for NS and for monitoring the effectiveness of NS therapy, especially in patients with nonreactive CSF-VDRL, excluding other neurologic diseases.